Optimalisasi Hasil Pertanian Desa Pujon melalui Pengembangan Produk Stik Susu oleh UMKM Lokal - Puspitasari, Dewi Sinta; Prista, Dynda; Hermawan, Agus; Winarno, Agung (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This study aims to optimize agricultural and livestock yields in Pujon District, Malang, the largest dairy production center, facing the dilemma of commodity price fluctuations and limited product diversification. The method implemented was the Participatory Local Social Development (PLSD) approach, focusing on holistic intervention (research, design, implementation, and evaluation). The research subject was the owner of Geofarm, Feri Fahrian Maulana. The program aimed to transform the dairy and vegetable processed product, Milk Stick (STISU), from a home industry scale into a competitive business unit. Program results demonstrate significant strengthening of the pre-digitalization foundation, including successful product R&D, HPP/BEP formulation, acceleration of legal compliance (NIB and Halal Certification), and the establishment of digital assets and informative packaging. Strategically, the evaluation prompted the consolidation of the STISU brand as a sub-brand under the master brand